Multidimensional pan-cancer analysis reveals the impact of PPIA on tumor epigenetic modifications and immune regulation - Yuanqian Yao; Xueqing Gong; Hui Li (Scientific Reports)
Abstract Peptidylprolyl isomerase A (PPIA) is a key molecule involved in various biological functions and has been implicated in multiple diseases. However, the biological significance of PPIA in pan-cancer remains unclear. We assessed the pan-cancer expression, prognostic value, and biological functions of PPIA through multiple databases and multidimensional analysis. We also investigated the correlation of PPIA with the immune microenvironment, epigenetic modifications, and drug sensitivity. Expression validation was performed using Western Blot (WB) and quantitative PCR (qPCR). PPIA was found to be highly expressed in most cancers and identified as a prognostic risk factor. The expression of PPIA in most cancers showed significant correlations with immune cell infiltration, major histocompatibility complex, immune checkpoints, tumor mutation burden, microsatellite instability, RNA modifications (including m1A, m5C, m6A), and DNA methylation sites. It was widely enriched in pathways such as Neuroactive ligand-receptor interaction, Calcium signaling pathway, and cAMP signaling pathway in the pan-cancer context. PPIA plays a pro-tumor role in various cancers and could serve as a potential biomarker for predicting cancer prognosis and the efficacy of immunotherapy.